Representações sociais acerca das drogas em crianças do 1º ciclo do ensino básico: implicações para a prevenção - Jorge Negreiros (2000)
The aim of the present study was to examine the representations about drugs held by 2-4 grade primary school students. Representations were elicited from 188 children aged between 7 and 13 years, drawn from seven schools located in Matosinhos, by asking them to draw and write their responses to questions relating to a story about losing and finding a bag of drugs. Drug users are described as individuals in deep physical and psychological degradation. Anyway, the phenomenon of drug use and abuse is not portrayed as a unitary and homogeneous one.